KONTESTASI KUASA DALAM PERDAGANGAN REMPAH DI PANTAI BARAT DAN SELATAN ACEH ABAD KE 18 HINGGA 19 M - Al Fairusy, Muhajir, MA; Pally Taran, Jovial, JPT; Feener, R. Michael, MF; haikal, haikal, hk (Paradigma: Jurnal Kajian Budaya, 2024)
The spice route has become a national discourse in the context of strengthening the Indonesian nation's maritime cultural identity. As one of the big nations, the archipelago was once a cross-national melting pot in the context of hunting and trading spices on an international scale. After all, spices were the prima donna commodity of their time, which raised the name of the archipelago to the international trade stage. This research was conducted to find out the history of the spice route in one of the archipelago regions, especially in Aceh. After all, Islam and the spice trade have become a part of the civilization of Aceh and the Archipelago. This research is a qualitative research, with an historical and anthropological method approach, in order to understand firsthand how the description of the spice trade route in Aceh, especially the western and southern regions of Aceh. The results showed that the West and South Coasts of Aceh had become the locus of one of the archipelago's spice trading centers from the late 18th century to the end of the 19th century AD. The progress of the spice trade was marked by the emergence of ports on the west coast, including the old Singkel port, Trumon , Susoh, Kuala Batu, Meulaboh, to Bandar Rigaih. The presence of the Trumon Kingdom, which was built from the rapid trade in spices and pepper, and the weakening influence and power of the Aceh Darussalam Kingdom, shows that there is a contestation of power between the Aceh Darussalam Kingdom, Dutch Colonial and local powers on the West coast. Among the spice commodities on the west coast of Aceh include; pepper, cloves, nutmeg, resin, and silk. However, the presence of spices on the West coast of Aceh contributed to the emergence of power contestation between the Kingdom of Aceh Darussalam, the Netherlands and the kingdoms on the West coast of Aceh, especially in the context of power struggles and spice commodities.